The predecessors influence on crop productivity and grain’s quality of soft winter wheat - Жемела, Г. П.; Шакалій, С. М. (Scientific Progress & Innovations, 2012)
The data about the influence of such predecessors as a bare fallow, peas and corn for silage on crop productivity and quality of soft winter wheat grain have been given. It has been noted that winter wheat grown after a bare fallow has the greatest crop productivity and the best grain quality indices. Corn for silage was the worst predecessor. An average crop productivity and grain quality was received after peas. Therefore, an important reserve of crop productivity increasing and its quality are scientifically justified choice of predecessor.